Open Access
Issue
Wuhan Univ. J. Nat. Sci.
Volume 28, Number 1, February 2023
Page(s) 15 - 19
DOI https://doi.org/10.1051/wujns/2023281015
Published online 17 March 2023

© Wuhan University 2023

Licence Creative CommonsThis is an Open Access article distributed under the terms of the Creative Commons Attribution License (https://creativecommons.org/licenses/by/4.0), which permits unrestricted use, distribution, and reproduction in any medium, provided the original work is properly cited.

0 Introduction

In 1960, Reed and Solomon[1] presented an important error correcting code, that is the so-called Reed-Solomon code. In 1987, Dur[2] defined a double extended Reed-Solomon code, which was later called projective Reed-Solomon code. He further studied the covering radius, decoding problem and the deep holes of projective Reed-Solomon codes in Refs.[3-5].

Now, we first recall the following definition of projective Reed-Solomon codes.

Definition 1[2]Let Fq be a finite field and let Fq={α1,,αq=0}. Then the projective Reed-Solomon codes of length q+1 with dimension k over Fq can defined as

P R S ( F q , k ) : = { ( f ( α 1 ) , f ( α 2 ) , , f ( α q ) , c k - 1 ( f ) ) F q q + 1 f ( x ) F q [ x ] , d e g f ( x ) k - 1 } (1)

where ck-1(f) is the coefficient of xk-1 in f(x).

Subsequently, we give the definition of deep holes of linear code C. To do this, for a received vector u, we first define the error distance d(u,C) and the covering radius ρ(C) of linear code C.

Definition 2[5] Let C be an [n,k] linear code over Fq. The error distance of a received vector uFqn to code C is defined by

d ( u , C ) : = m i n v C { d ( u , v ) } ,

where d(u,v) is the Hamming distance of u and v.

Clearly, d(u,C)=0 if and only if uC .

For a given projective Reed-Solomon code PRS(Fq,k), we define the Lagrange interpolation polynomial u(x) of the first q components of received vector u=(u1,,uq,uq+1)Fqq+1 by

u ( x ) : = i = 1 q u i j = 1 j i q x - α j α i - α j (2)

Obviously, one has u(αi)=ui for 1iq and further d(u,PRS(Fq,k))=0 if and only if degu(x)k-1,ck-1(u(x))=uq+1.

Definition 3 [5]Let C be an [n,k] linear code over Fq. Then

ρ ( C ) : = m a x { d ( u , C ) u F q n }

is called as the covering radius of C.

In fact, there is a well known conjecture on the covering radius of projective Reed-Solomon codes.

Conjecture 1[6] Let k be an integer with 2kq-2. Suppose 2q,k{2,q-2}, then

ρ ( P R S ( F q , k ) ) = q - k + 1 .

otherwise, ρ(PRS(Fq,k))=q-k.

Now we can propose the definition of deep holes of linear code as follows.

Definition 4 [7] Let C be a [n,k] linear code over Fq. If the received vector u such that d(u,C)=ρ(C), then u is called a deep hole of C.

In 2016, Zhang et al[8] proved that (u(α1),,u(αq),0)+PRS(Fq,k) is a deep hole of projective Reed-Solomon codes PRS(Fq,k) by solving the subset problem over finite field Fq , where u(x)=axk+fk-1(x), aFq* , and fk-1(x) is a polynomial over Fq with degree no more than k-1. Then, in 2017, Kaipa [9] studied the deep holes of projective Reed-Solomon codes PRS(Fq,q-2) over Fq with odd characteristic. In 2018, Xu et al[10] proved that (u(α1),,u(αq-1),0)+PRS(Fq*,k) is a deep hole of PRS(Fq*,k), where u(x)=axq-2+fk-2(x) with aFq* and fk-2(x) being a polynomial over Fq whose degree not exceed k-2. In 2020, Zhang et al[6] completely determined all the deep holes of projective Reed-Solomon codes PRS(Fq,q-3) by using the polynomial theory over finite fields and applying the finite geometry method. Meanwhile, they raised the following open problem.

Problem 1[6] For a given projective Reed-Solomon code PRS(Fq,k), how to determine all its deep holes?

More results on deep holes of Reed-Solomon codes, one can see Refs.[11-15].

The main purpose of this paper is to study problem 1 over finite fields with even characteristic. Now, we describe the main theorem of this paper as following.

Theorem 1   Let Fq be finite field with even characteristic, k{2,q-2}. Let u(x) be the Lagrange interpolation polynomial of the first q components of the received vector uFqq+1 . Suppose that the (q+1)-th component of u is 0, and

u ( x ) = λ x k + f k - 2 ( x )

or

u ( x ) = λ x q - 2 + f k - 2 ( x ) ,

where λFq* , and fk-2(x) is a polynomial over Fq with degree no more than k-2. Then the received vector u is a deep hole of PRS(Fq,k).

Actually, Theorem 1 partially solved Problem 1 raised by Ref.[6]. This paper is organized as follows. In Section 1, we supply some preliminary lemmas that are needed in the proof of Theorem 1. Then in Section 2, we present the proof of Theorem 1.

1 Preliminary Lemmas

In this section, we give some lemmas needed in the proof of Theorem 1. First, a formula of a special determinant over finite fields given as follows.

Lemma 1   Let {β1,,βn}Fq*.Then

d e t ( 1 1 1 β 1 2 β 2 2 β n 2 β 1 n β 2 n β n n ) = ( i = 1 n β i - 1 ) ( i = 1 n β i ) 1 i < j n ( β j - β i ) .

Proof   Noticed that

d e t ( 1 1 1 1 β 1 β 2 β n x β 1 2 β 2 2 β n 2 x 2 β 1 n β 2 n β n n x n ) = ( i = 1 n ( x - β i ) ) 1 i < j n ( β j - β i ) .

Then, one can immediately get Lemma 1 by comparing the coefficients of x on both sides of the above equality. This completes the proof of Lemma 1.

Next, we prove the following result on subset sum over finite fields with even characteristic.

Lemma 2   Let Fq be finite field with even characteristic. If l{1,2,q-3,q-2}, then the sum of any l different elements in Fq* is nonzero.

Proof   The Lemma 2 obviously holds when l=1. Put Fq*={γ1,,γq-1}. Now we give the proof for l=2,q-3,q-2, respectively.

Case 1. l=2. Without loss of generality, one can take two distinct elements of Fq* as γ1,γ2. Since Fq is a finite filed with characteristic 2, hence one can get

γ 1 + γ 2 = γ 1 - γ 2 0 .

Case 2. l=q-3. Without loss of generality, one can also choose q-3 distinct elements of Fq* as γ1,,γq-3. Notice that Fq is a finite filed with characteristic 2, therefore

i = 1 q - 3 γ i = i = 1 q - 1 γ i - γ q - 2 - γ q - 1 = γ q - 2 - γ q - 1 ,

and also γq-2γq-1, thus i=1q-3γi0.

Case 3. l=q-2. Without loss of generality, one can pick q-2 distinct elements γ1,,γq-2Fq*. The character of Fq is 2 can tell us that

i = 1 q - 2 γ i = i = 1 q - 1 γ i - γ q - 1 = γ q - 1 0 .

The proof of Lemma 2 is complete.

In 1991, Dur[3] had given the following result on covering radius of projective Reed-Solomon codes over finite fields with even characteristic by using the finite geometry method.

Lemma 3[3]Let 2q, k{2,q-2}. Then

ρ ( P R S ( F q , k ) ) = q - k + 1 .

Finally, we recall a theorem on the received vector u is whether or not a deep hole of maximal distance separable code C.

Lemma 4[16] Let C be [n,k] maximal distance separable code over finite field Fq. If the covering radius ρ(C) of code C is n-k, then the received vector uFqn is a deep hole of C if and only if any k+1 columns of the (k+1)×n matrix (Gu) is linearly independent, where G is the generator matrix of code C.

2 Proof of Theorem 1

In this section, we use the lemmas presented in Section 1 to give the proof of Theorem 1.

Proof   Let Fq={x1,,xq=0}. By (1) and (2), one can immediately get that

( G u ) = ( 1 1 1 0 x 1 x 2 x q 0 x 1 2 x 2 2 x q 2 0 x 1 k - 1 x 2 k - 1 x q k - 1 1 u ( x 1 ) u ( x 2 ) u ( x q ) 0 ) : = ( G ¯ 1 , G ¯ 2 , , G ¯ q + 1 ) .

Assume that G¯j1,G¯j2,,G¯jk+1 are any k+1 columns of (Gu), where j1,j2,,jk+1 are arbitrary k+1 integers with 1j1<j2<<jk+1q+1. To complete the proof of the Theorem, it suffices to show

d e t ( G ¯ j 1 , G ¯ j 2 , , G ¯ j k + 1 ) 0 (3)

To do so, we give the proof as the following eight cases.

Case 1. u(x)=λxk+fk-2(x). The four cases are considered as follows.

Case 1-1. jk+1<q. At this time, one has

d e t ( G ¯ j 1 , G ¯ j 2 , , G ¯ j k + 1 ) = d e t ( 1 1 1 x j 1 x j 2 x j k + 1 x j 1 2 x j 2 2 x j k + 1 2 x j 1 k - 1 x j 2 k - 1 x j k + 1 k - 1 u ( x j 1 ) u ( x j 2 ) u ( x j k + 1 ) ) [ = λ 1 s < t k + 1 ( x j t - x j s ) 0 ] (4)

Case 1-2. jk+1=q. By xq=0, one can know that

d e t ( G ¯ j 1 , G ¯ j 2 , , G ¯ j k + 1 ) = λ d e t ( 1 1 1 1 x j 1 x j 2 x j k 0 x j 1 2 x j 2 2 x j k 2 0 x j 1 k - 1 x j 2 k - 1 x j k k - 1 0 x j 1 k x j 2 k x j k k 0 ) = ( - 1 ) k + 2 λ ( i = 1 k x j i ) 1 s < t k ( x j t - x j s ) 0 (5)

Case 1-3. jkq-1,jk+1=q+1. One can deduce that

d e t ( G ¯ j 1 , G ¯ j 2 , , G ¯ j k + 1 ) = λ d e t ( 1 1 1 0 x j 1 x j 2 x j k 0 x j 1 2 x j 2 2 x j k 2 0 x j 1 k - 1 x j 2 k - 1 x j k k - 1 1 x j 1 k x j 2 k x j k k 0 ) = ( - 1 ) 2 k + 1 λ ( i = 1 k x j i ) 1 s < t k ( x j t - x j s ) .

And also 2|q,k{2,q-2}, it follows from Lemma 2 that i=1kxji0. Then one can derive that

d e t ( G ¯ j 1 , G ¯ j 2 , , G ¯ j k + 1 ) 0 (6)

Case 1-4. jk=q,jk+1=q+1. By xq=0, one can derive that

d e t ( G ¯ j 1 , G ¯ j 2 , , G ¯ j k + 1 ) ( 1 1 1 1 0 x j 1 x j 2 x j k - 1 0 0 x j 1 2 x j 2 2 x j k - 1 2 0 0 x j 1 k - 1 x j 2 k - 1 x j k - 1 k - 1 0 1 x j 1 k x j 2 k x j k - 1 k 0 0 ) = λ d e t = ( - 1 ) 3 k + 2 λ ( i = 1 k - 1 x j i ) ( i = 1 k - 1 x j i ) 1 s < t k - 1 ( x j t - x j s )

Notice that k-1=1,q-3, by Lemma 2, one can get i=1k-1xji0. It follows that

d e t ( G ¯ j 1 , G ¯ j 2 , , G ¯ j k + 1 ) 0 (7)

Case 2.v(x)=λxq-2+fk-2(x). One only need to deal with the four cases as follows.

Case 2-1. jk+1<q. Notice that for any integer i with 1ik+1, one has xjiq-2=xji-1. It then follows that

d e t ( G ¯ j 1 , G ¯ j 2 , , G ¯ j k + 1 ) = λ d e t ( 1 1 1 x j 1 x j 2 x j k + 1 x j 1 2 x j 2 2 x j k + 1 2 x j 1 k - 1 x j 2 k - 1 x j k + 1 k - 1 x j 1 - 1 x j 2 - 1 x j k + 1 - 1 ) = ( - 1 ) k λ ( i = 1 k + 1 x j i - 1 ) d e t ( 1 1 1 x j 1 x j 2 x j k + 1 x j 1 2 x j 2 2 x j k + 1 2 x j 1 k x j 2 k x j k + 1 k ) = ( - 1 ) k λ ( i = 1 k + 1 x j i - 1 ) 1 s < t k + 1 ( x j t - x j s ) 0 (8)

Case 2-2. jk+1=q. Since xjiq-2=xji-1(1ik) and xq=0, so

d e t ( G ¯ j 1 , G ¯ j 2 , , G ¯ j k + 1 ) = λ d e t ( 1 1 1 1 x j 1 x j 2 x j k 0 x j 1 2 x j 2 2 x j k 2 0 x j 1 k - 1 x j 2 k - 1 x j k k - 1 0 x j 1 - 1 x j 2 - 1 x j k - 1 0 ) = ( - 1 ) k + 2 λ ( i = 1 k x j i - 1 ) d e t ( x j 1 2 x j 2 2 x j k 2 x j 1 3 x j 2 3 x j k 3 x j 1 k x j 2 k x j k k 1 1 1 )

Then by Lemma 1, one can derive that

d e t ( G ¯ j 1 , G ¯ j 2 , , G ¯ j k + 1 ) = ( - 1 ) 2 k + 1 λ ( i = 1 k x j i - 1 ) 1 s < t k ( x j t - x j s ) .

Now note that k{2,q-2} and xji-1Fq*. Then Lemma 2 can tell us that i=1kxji-10. This implies

d e t ( G ¯ j 1 , G ¯ j 2 , , G ¯ j k + 1 ) 0 (9)

Case 2-3. jkq-1,jk+1=q+1. Since xjiq-2=xji-1(1ik), one then can deduce that

d e t ( G ¯ j 1 , G ¯ j 2 , , G ¯ j k + 1 ) = λ d e t ( 1 1 1 0 x j 1 x j 2 x j k 0 x j 1 2 x j 2 2 x j k 2 0 x j 1 k - 1 x j 2 k - 1 x j k k - 1 1 x j 1 - 1 x j 2 - 1 x j k - 1 0 ) = ( - 1 ) 2 k + 1 λ ( i = 1 k x j i - 1 ) d e t ( x j 1 x j 2 x j k x j 1 2 x j 2 2 x j k 2 x j 1 k - 1 x j 2 k - 1 x j k k - 1 1 1 1 ) = ( - 1 ) 3 k λ ( i = 1 k x j i - 1 ) 1 s < t k ( x j t - x j s ) 0 (10)

Case 2-4. jk =q,jk+1=q+1. Owing to xjiq-2=xji-1(1ik-1) and xq=0, one then can get

= λ d e t ( 1 1 1 1 0 x j 1 x j 2 x j k - 1 0 0 x j 1 2 x j 2 2 x j k - 1 2 0 0 x j 1 k - 1 x j 2 k - 1 x j k - 1 k - 1 0 1 x j 1 - 1 x j 2 - 1 x j k - 1 - 1 0 0 ) = ( - 1 ) 3 k + 2 λ ( i = 1 k - 1 x j i - 1 ) d e t ( x j 1 2 x j 2 2 x j k - 1 2 x j 1 3 x j 2 3 x j k - 1 3 x j 1 k - 1 x j 2 k - 1 x j k - 1 k - 1 1 1 1 )

By Lemma 1, one can deduce that

d e t ( G ¯ j 1 , G ¯ j 2 , , G ¯ j k + 1 ) = ( - 1 ) 4 k λ ( i = 1 k - 1 x j i - 1 ) ( i = 1 k - 1 x j i - 1 ) ( i = 1 k - 1 x j i - 1 ) 1 s < t k - 1 ( x j t - x j s ) = λ ( i = 1 k - 1 x j i - 1 ) 1 s < t k - 1 ( x j t - x j s )

Notice that k-1=1,q-3 and xji-1Fq*. Applying Lemma 2, one can obtain i=1k-1xji-10. It yields that

d e t ( G ¯ j 1 , G ¯ j 2 , , G ¯ j k + 1 ) 0 (11)

Thus, (3) can be immediately obtained from (4)-(11), that is, any k+1columns of (Gu) are linearly independent. On the other hand, PRS(Fq,k) is a maximal distance separable code and Lemma 3 also tell us that the covering radius of PRS(Fq,k) is

ρ ( P R S ( F q , k ) ) = q - k + 1 = n - k .

Therefore, by Lemma 4, one can know that u is a deep hole of projective Reed-Solomon codes PRS(Fq,k). This finish the proof of Theorem 1.

References

  1. Reed S, Solomon G. Polynomial codes over certain finite fields[J]. Journal of the Society for Industrial and Applied Mathematics, 1960, 8(2): 300-304. [CrossRef] [MathSciNet] [Google Scholar]
  2. Dur A. The automorphism groups of Reed-Solomon codes[J]. J Combin Theory, Ser A, 1987, 44(1): 69-82. [CrossRef] [MathSciNet] [Google Scholar]
  3. Dur A. The decoding of extended Reed-Solomon codes[J]. Discrete Math, 1991, 90(1): 21-40. [CrossRef] [MathSciNet] [Google Scholar]
  4. Dur A. Complete decoding of doubly-extended Reed-Solomon codes of minimum distance 5 and 6[J]. Discrete Appl Math, 1991, 33(1/2/3): 95-107. [CrossRef] [MathSciNet] [Google Scholar]
  5. Dur A. On the covering radius of Reed-Solomon codes[J]. Discrete Math, 1994, 126(1/2/3): 99-105. [CrossRef] [MathSciNet] [Google Scholar]
  6. Zhang J, Wan D Q, Kaipa K. Deep holes of projective Reed-Solomon codes[J]. IEEE Trans Inform Theory, 2020, 66(4): 2392-2401. [CrossRef] [MathSciNet] [Google Scholar]
  7. Cheng Q, Murray E. On deciding deep holes of Reed-Solomon codes[J]. Lecture Notes in Comput Sci, 2007, 4484: 296-305. [CrossRef] [Google Scholar]
  8. Zhang J, Wan D Q. On deep holes of projective Reed-Solomon codes[C]//2016 IEEE International Symposium Information Theory. Washington D C: IEEE, 2016: 925-929. [Google Scholar]
  9. Kaipa K. Deep holes and MDS extensions of Reed-Solomon codes[J]. IEEE Trans Inform Theory, 2017, 63(8): 4940-4948. [CrossRef] [MathSciNet] [Google Scholar]
  10. Xu X F, Hong S F, Xu Y C. On deep holes of primitive projective Reed-Solomon codes[J]. Sci Sin Math, 2018, 48(8): 1087-1094. [CrossRef] [Google Scholar]
  11. Hong S F, Wu R J. On deep holes of generalized Reed-Solomon codes[J]. AIMS Math, 2016, 1(2): 96-101. [CrossRef] [Google Scholar]
  12. Keti M, Wan D. Deep holes in Reed-Solomon codes based on Dickson polynomials[J]. Finite Fields Appl, 2016, 40: 110-125. [CrossRef] [MathSciNet] [Google Scholar]
  13. Li Y J, Wan D Q. On error distance of Reed-Solomon codes[J]. Sci China Ser A, 2008, 51(11): 1982-1988. [CrossRef] [MathSciNet] [Google Scholar]
  14. Li Y J, Zhu G Z. On the error distance of extended Reed-Solomon codes[J]. Adv Math Commun, 2016, 10(2): 413-427. [CrossRef] [MathSciNet] [Google Scholar]
  15. Wu R J, Hong S F. On deep holes of standard Reed-Solomon codes[J]. Science China Math, 2012, 55(12): 2447-2455. [NASA ADS] [CrossRef] [MathSciNet] [Google Scholar]
  16. Zhuang J C, Cheng Q, Li J Y. On determing deep holes of generalized Reed-Solomon codes[J]. IEEE Trans Inform Theory, 2016, 62(1): 199-207. [CrossRef] [MathSciNet] [Google Scholar]

Current usage metrics show cumulative count of Article Views (full-text article views including HTML views, PDF and ePub downloads, according to the available data) and Abstracts Views on Vision4Press platform.

Data correspond to usage on the plateform after 2015. The current usage metrics is available 48-96 hours after online publication and is updated daily on week days.

Initial download of the metrics may take a while.